2000
DOI: 10.1177/0021886300361003
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Psychological Typology of Entrepreneurship Using Business Founders

Abstract: This study follows upon previous research among established entrepreneurs indicating that a four-way psychological typology (i.e., personal achievers, real managers, expert idea generators, and empathic supersalespeople) predicts firm growth. It extends support for the typology to the venture initiation phase and to a student population. The results confirm that those students who are characterized by one or more of the types are more likely to be entrepreneurs after graduation. Measures of entrepreneurial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 51 publications
1
56
0
11
Order By: Relevance
“…They have also shown that differences in psychological profiles determine why some individuals, and not others, identify certain entrepreneurial opportunities and behave differently toward these opportunities. These psychological attributes are also related to entrepreneurial orientation (Begley and Boyd, 1987;Miller and Droge, 1986;Miller et al, 1982;Miner, 2000), defined as a person's willingness to take the risks associated with creating new companies and exploit these opportunities. For example, compared with non-founders, business founders have higher scores on risk-taking propensity and tolerance of ambiguity (Begley & Boyd).…”
mentioning
confidence: 99%
“…They have also shown that differences in psychological profiles determine why some individuals, and not others, identify certain entrepreneurial opportunities and behave differently toward these opportunities. These psychological attributes are also related to entrepreneurial orientation (Begley and Boyd, 1987;Miller and Droge, 1986;Miller et al, 1982;Miner, 2000), defined as a person's willingness to take the risks associated with creating new companies and exploit these opportunities. For example, compared with non-founders, business founders have higher scores on risk-taking propensity and tolerance of ambiguity (Begley & Boyd).…”
mentioning
confidence: 99%
“…Some approaches associate specifically the entrepreneurial leadership style to narcissism traits (Mathieu & St-Jean, 2013) and internal locus of control (Miner, 2000;Mueller & Thomas, 2001). Beyond the personality traits, behavioural and psychological aspects related to the entrepreneurial leadership style probably lead the entrepreneur to the acquisition of management, communication and persuasion skills (Mueller & Goić, 2002;Schmidt & Bohnenberger, 2009;Nassif et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…More than opening a business, the entrepreneurial action is directly related to aspects of personality [cognitive development, adaptation, traits, interests, impulses, self-concept, capacity and emotional patterns (see, Schultz & Schultz, 2006)] and human values [guide for actions and cognitive expression of basic needs (see, Gouveia et al, 2014)] (Littunen, 2000;Miner, 2000;Kristiansen & Indarti, 2004;Santos, 2008;Alves & Bornia, 2011;Brandstätter, 2011;Abebe, 2012;Barba-Sánchez & Atienza-Sahuquillo, 2012;Karabey, 2012;Minello & Scherer, 2012;Mathieu & St-Jean, 2013).…”
Section: Entrepreneurial Behaviour Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being active rather than passive, particularly in relation to opportunity exploitation: taking the initiative, even at high risk, rather than settling for routine; workaholic tendencies; seeking control over others/situations rather than being controlled; aversion to passive, unquestioning conformity; see also 'need for achievement'; 'type A' personalities (Collins, 2004;Harper, 1996;Miner, 2000;Stewart et al, 1999;Cromie and O'Donaghue, 1992;Shane, 2003).…”
Section: (A)mentioning
confidence: 99%